2016
DOI: 10.1590/1414-431x20165181
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training modulates T cell activation in elderly women with knee osteoarthritis

Abstract: Osteoarthritis of the knee (kOA) is a disease that mainly affects the elderly and can lead to major physical and functional limitations. However, the specific effects of walking, particularly on the immune system, are unknown. Therefore, this study aimed to analyze the effect of 12 weeks of walking (3×/week) on the leukocyte profile and quality of life (QL) of elderly women with kOA. Sixteen women (age: 67±4 years, body mass index: 28.07±4.16 kg/m2) participated in a walking program. The variables were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…A previous study suggested that PD-1 may be involved in the regulation of immune responses, and therefore, may be a promising target for immunotherapy. 62 Gomes and colleagues 18 suggested that KOA is a disease with immunological systemic consequences, and aerobic training can modulate immune markers of activated lymphocytes in KOA patients and lead to improvements in symptoms. PD-1 is a cell surface protein that has a role in regulating the immune response by down-regulating the immune system, and is a key serum biomarker in the process and treatment of KOA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study suggested that PD-1 may be involved in the regulation of immune responses, and therefore, may be a promising target for immunotherapy. 62 Gomes and colleagues 18 suggested that KOA is a disease with immunological systemic consequences, and aerobic training can modulate immune markers of activated lymphocytes in KOA patients and lead to improvements in symptoms. PD-1 is a cell surface protein that has a role in regulating the immune response by down-regulating the immune system, and is a key serum biomarker in the process and treatment of KOA.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In addition, immune mechanisms and inflammatory responses, including the serum brain-derived neurotrophic factor (BDNF), interferon gamma (IFN-g), serum programmed death 1 (PD-1), and T-cell Ig-and mucin-domain-containing molecule-3 (TIM-3), are believed to play a critical role in osteoarthritis (OA). 18,19 For example, Simão and colleagues 20 have found a significant positive correlation between plasma BDNF concentrations and self-reported pain (Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC]) in KOA patients. IFN-g signalling mediates spinal microglia activation driving neuropathic pain.…”
mentioning
confidence: 99%
“…The reversal of this condition can be achieved by physical exercise. A study of our research group (Gomes et al, 2016) showed that the increased physical performance in elderly women with kOA may be related to the immunomodulatory effect of exercise. In addition, physical exercise induces a cascade of molecular and cellular processes that support brain plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Forty-nine studies met our eligibility criteria for objective 1, review of exercise prescriptions (figure 1). 28 29 38–83 Twenty-three RCTs compared an aerobic exercise group to a non-exercising control group, 15 RCTs compared groups completing different types of exercise and 11 studies compared outcomes before and after aerobic exercise in one group. Fourteen studies reported a marker of cardiovascular health and/or systemic inflammation and were included in various meta-analyses.…”
Section: Resultsmentioning
confidence: 99%